Nilai Pendidikan Akhlak dalam Film Animasi Nussa dan Rara sebagai Media Pembelajaran Materi Akidah Akhlak di MI Nurul Huda Srimulyo - Hasan, Sholeh; Hidayati, Lilik (Prodi Pendidikan Agama Islam, 2023)
The Value of Moral Education in Nussa and Rara Animation Films as Learning Media for Moral Aqidah Materials at Mi Nurul Huda Srimulyo. This journal discusses the value of moral education in the Nussa and Rara animation as a teaching medium for the subject of faith and morality at MI Nurul Huda Srimulyo. The purpose of this study is to determine the values contained in the Nussa and Rara animation regarding moral education as a teaching medium at MI Nurul Huda Srimulyo. The underlying problem is that the Nussa and Rara film serves as a response to parents' concerns about the lack of educational programs for children. Many religious values are presented in high-quality animated films, which can attract children's interest. This research is of a descriptive nature with a qualitative approach. The research methods used are observation, interviews, and documentation. The results of the study can be summarized as follows: the Nussa and Rara animation contains moral education values that can be used as an educational tool for students, particularly in Islamic religious education. The value of the Nussa and Rara animation in terms of moral education as a teaching medium at MI Nurul Huda Srimulyo is that it helps students grasp the taught material more easily.